Scandium-decorated MOF-5 as potential candidates for room-temperature hydrogen storage: a solution for the clustering problem in MOFs - Dixit, Mudit; Maark, Tuhina Adit; Ghatak, Kamalika; Ahuja, Rajiv; Pal, Sourav (Journal of Physical Chemistry C, 2012)
Transition-metal-based systems show promising binding energy for hydrogen storage but suffer from clustering problem. The effect of light transition metal (M = Sc, Ti) decoration, boron substitution on the hydrogen storage properties of MOF-5, and clustering problem of metals has been investigated using ab initio density, functional theory. Our results of solid-tate calculations reveal that whereas Ti clusters strongly Sc atoms do not suffer from this problem when decorating MOF-5. Boron substitution on metal-decorated MOF-5 enhances the interaction energy of both the metals with MOF-5. Sc-decorated MOF-5 shows a hydrogen storage capacity of 5.81 wt % with calculated binding energies of 20-40 kJ/mol, which ensures the room-teniperature applicability of this hydrogen storage material.